Getting others to do things: A pragmatic typology of recruitments - Enfield, N. J. 1966-; Rossi, Giovanni; Floyd, Simeon (Studies in diversity linguistics, 2020)
Getting others to do things is a central part of social interaction in any human society. Language is our main tool for this purpose. In this book, we show that sequences of interaction in which one person’s behaviour solicits or occasions another’s assistance or collaboration share common structural properties that provide a basis for the systematic comparison of this domain across languages. The goal of this comparison is to uncover similarities and differences in how language and other conduct are used in carrying out social action around the world, including different kinds of requests, orders, suggestions, and other actions brought together under the rubric of recruitment